2005
DOI: 10.2337/diabetes.54.1.234
|View full text |Cite
|
Sign up to set email alerts
|

Aldose Reductase Inhibition Counteracts Oxidative-Nitrosative Stress and Poly(ADP-Ribose) Polymerase Activation in Tissue Sites for Diabetes Complications

Abstract: This study evaluated the effects of aldose reductase inhibition on diabetes-induced oxidative-nitrosative stress and poly(ADP-ribose) polymerase (PARP) activation. In animal experiments, control and streptozotocin-induced diabetic rats were treated with or without the aldose reductase inhibitor (ARI) fidarestat (16 mg ⅐ kg ؊1 ⅐ day ؊1 ) for 6 weeks starting from induction of diabetes. Sorbitol pathway intermediate, but not glucose, accumulation in sciatic nerve and retina was completely prevented in diabetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
137
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 160 publications
(150 citation statements)
references
References 69 publications
8
137
1
3
Order By: Relevance
“…10) (El-Remessy, 2003a;Graier et al, 1999;Graier et al, 1997;Graier et al, 1996) resulting in peroxynitrite formation. Research demonstrating increased levels of the peroxynitrite biomarker nitrotyrosine in retinas of diabetic patients and experimental animal models supports this concept and implies a role for peroxynitrite in the development of diabetic complications (Abu El-Asrar et al, 2004;Du et al, 2002;ElRemessy, 2003b;Kowluru and Odenbach, 2004;Obrosova et al, 2005). Studies in animal and tissue culture models have demonstrated that increased peroxynitrite formation is directly correlated with diabetes, high glucose-induced VEGF expression, and increased retinal vascular permeability (El-Remessy, 2003a;El-Remessy, 2003b;El-Remessy et al, 2006;El-Remessy et al, 2005).…”
Section: Oxidative Stress and Diabetic Retinopathymentioning
confidence: 94%
“…10) (El-Remessy, 2003a;Graier et al, 1999;Graier et al, 1997;Graier et al, 1996) resulting in peroxynitrite formation. Research demonstrating increased levels of the peroxynitrite biomarker nitrotyrosine in retinas of diabetic patients and experimental animal models supports this concept and implies a role for peroxynitrite in the development of diabetic complications (Abu El-Asrar et al, 2004;Du et al, 2002;ElRemessy, 2003b;Kowluru and Odenbach, 2004;Obrosova et al, 2005). Studies in animal and tissue culture models have demonstrated that increased peroxynitrite formation is directly correlated with diabetes, high glucose-induced VEGF expression, and increased retinal vascular permeability (El-Remessy, 2003a;El-Remessy, 2003b;El-Remessy et al, 2006;El-Remessy et al, 2005).…”
Section: Oxidative Stress and Diabetic Retinopathymentioning
confidence: 94%
“…are able to suppress the activation of PARP in the cardiovascular system (Cuzzocrea et al 2004, although whether such effects are also present in diabetic models remains to be seen. It is noteworthy in this respect that in preclinical studies, administration of the aldose reductase inhibitors sorbinil or fidarestat to diabetic rats not only corrected diabetesinduced depletion of glutathione and ascorbate, downregulation of SOD activity and accumulation of lipid peroxidation products in the peripheral nerve, counteracted superoxide formation in vasa nervorum and was effective against multiple indices of diabetesassociated retinal oxidative and nitrosative stress, but also inhibited poly(ADP-ribose) accumulation (a marker of PARP activation) in diabetic nerve and retina (Obrosova et al 2004d). Similar results were obtained with FP15, a novel peroxynitrite decomposition catalyst compound ).…”
Section: Discussionmentioning
confidence: 99%
“…Reports that ARI treatment prevents oxidative damage to lipids and DNA in nerves of rats with diabetes 66,67 indicate that increased flux through the polyol pathway contributes to oxidative stress, and implicates Schwann cells in causing this oxidative stress, as they express aldose reductase. Moreover, increased flux through the polyol pathway depletes cytosolic NADPH and subsequently reduces levels of glutathione (an important antioxidant), leaving neurons and Schwann cells vulnerable to toxic oxygen free radicals and peroxides 61 .…”
Section: Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%